The Effect of n-3 Polyunsaturated Fatty Acids on the Components of Metabolic Syndrome, a Systematic Review and Meta-Analysis of Randomized Controlled Trials (P08-037-19). (24th October 2019) - Huo, Tianyao; Yang, Changjun; Cardel, Michelle; Brown, Andrew; Gurka, Matthew
Abstract: Objectives: Intake of n-3 polyunsaturated fatty acids (PUFAs) has been reported to provide various benefits for patients with metabolic syndrome (MetS), such as reducing blood pressure and improving blood lipids, but results are inconsistent. This study aimed to investigate the effect of n-3 PUFA intake on components of MetS. Methods: We searched PubMed, Scopus, Web of Sciences, and Cochrane databases up to June 2018 for randomized trials at least 30 days long comparing n-3 PUFAs with a control in patients diagnosed with MetS (PROSPERO registration ID: CRD42017072332). The outcomes include body mass index, systolic and diastolic blood pressure, triglyceride, high-density lipoprotein cholesterol, and fasting blood glucose. Mean differences post-intervention or mean change from baseline were combined using random-effects models; confirmation of within-study effect sizes is ongoing. Results: A total of 14 trials were identified. The pooled results showed n-3 PUFA intake reduced systolic blood pressure by 3.92 mmHg (95%CI: –6.89, –0.96, P-value = 0.009, I2 = 34%, 9 trials) and diastolic blood pressure by 2.81 mmHg (95%CI: –4.26, –1.36, P-value = 0.0001, I2 = 15%, 8 trials). Body mass index was lower in the n-3 PUFA group by 3.19 kg/m2 (95%CI: –6.16, –0.22, P-value = 0.04, I2 = 97%, 7 trials) compared to the control group. Triglyceride levels in n-3 PUFA groups were significantly lower than the control when pooling trials with post intervention data only (–33.13 mg/dL, 95%CI: –49.44, –16.81, P-value < 0.0001, I2 = 71%, 6 trials), but the overall effect was non-significant when including studies with pre-post data (P-value = 0.08). The n-3 PUFA intake did not significantly alter high-density lipoprotein cholesterol (P-value = 0.71) or fasting glucose (P-value = 0.36). Conclusions: Our preliminary results provide evidence for beneficial effects of n-3 PUFAs on reducing blood pressure and improving weight control in patients with MetS, with less certain results for triglycerides. Sensitivity and confirmatory analyses are in progress to test the robustness of results under different effect-size assumptions and to investigate sources of heterogeneity. Most of the included trials had small sample sizes. Randomized trials with higher quality and larger scale are needed to confirm the findings. Funding Sources: The authors received no funding for this specific work. Other funding support includes: AWB: NIH R25DK099080, R25HL124208. Supporting Tables, Images and/or Graphs